Effects of fowlpox virus infection on lipid metabolism in cultured chicken embryo cells. - Buttke, T M (1982)
Lipid biosynthesis was measured in cultured chicken embryo cells after infection with fowlpox virus. Between 24 and 72 h postinfection, fowlpox virus-infected cells incorporated less [14C]acetate and 3H2O into fatty acids and sterols than did mock-infected cells, demonstrating a virus-dependent inhibition of general lipid metabolism. Two specific effects of fowlpox virus infection were an accumulation of C-4 alkylated sterol intermediates and inhibition of monounsaturated fatty acid biosynthesis.